Nosocomial blood stream infections in a neonatal intensive care unit in Ankara, Turkey - Baş, Ahmet Yağmur; Demirel, Nihal; Zenciroglu, Ayşegül; Göl, Neşe; Tanir, Gönül (The Turkish Journal of Pediatrics, 2010)
Nosocomial blood stream infections continue to be a cause of high mortality and morbidity in newborn intensive care units (NICUs). Identification of the causative microorganisms and their antimicrobial sensitivities will guide the selection of appropriate empirical treatment. We prospectively evaluated culture-proven nosocomial sepsis cases and antibiotic sensitivity patterns seen in the NICU of Dr. Sami Ulus Children's Hospital, in Ankara, Turkey during a six-year period (2000-2006). A total of 106 nosocomial sepsis attacks were found in 100 patients, with 72 of them preterm. Gram-negative bacteria were isolated at a rate of 70.8%, gram-positive at 22.6% and Candida species (spp.) at 6.6%. The most commonly isolated microorganisms were, in order of frequency, Klebsiella spp. (39.6%), Pseudomonas aeruginosa (11.3%) and Coagulase-negative staphylococci (9.4%). During the study, 12 of the 28 term babies (42.9%) and 26 of the 72 preterm babies (36.1%) died due to nosocomial sepsis, with a mortality rate of 38%. Resistance to ampicillin was 100%, to cefotaxime 88%, to gentamicin 73%, and to amikacin 23% in gram-negative bacteria. No carbapenem resistance was found except for P. aeruginosa (25%). Resistance to penicillin was 100% and clindamycin 58.3% in gram-positive bacteria. No glycopeptide or carbapenem resistance was found. In conclusion, nosocomial sepsis still has a high mortality rate. Gram-negative bacteria were the most commonly isolated microorganisms with Klebsiella spp. being dominant. All gram-negative species were resistant to ampicillin, and all gram-positive bacteria were resistant to penicillin. No glycopeptide or carbapenem resistance was found in gram-positive bacteria. In gram-negative bacteria, low amikacin and high gentamicin and cephalosporin resistances were found. No carbapenem resistance was found except for P. aeruginosa. Restricted and alternate antibiotic usage policies seem important for the resistance problem.